PERSEPSI AKUNTAN DAN MANNER TENTANG ETIKA BISNIS - Yvonne Augustine S. (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
The fuction of accountant and manager was different so there maybe differences perception in understanding and practising the Business ethics. This research uses 148 Public Accountant, Management Accoountant and Educa-tional Accountant and Managers, total 317 respondentsThe reliability test of Business Ethics range from 0,87 - 0,93 and the validity was above significancy level 0-05 the data was distributed normally. This research found that there was no differences between Accountant and manager perception on under-standing and practicing businees ethics.Keyword: Business Ethics, accountant and manager perceptions